2016
DOI: 10.1002/dmrr.2817
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and psychological challenges of increasing physical activity and exercise in patients at risk of diabetic foot ulcers: a critical review

Abstract: Obesity and a sedentary lifestyle are common challenges among individuals at risk of diabetic foot ulcers (DFUs). While substantial research exists on physical activity interventions in adults with diabetes, those at greatest risk for foot ulceration were often excluded or not well-represented. Both at-risk patients and their clinicians may be hesitant to increase physical activity due to their perception of DFU risks. Physical activity is not contraindicated for those at risk of DFU, yet patients at risk pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 146 publications
(177 reference statements)
0
50
0
2
Order By: Relevance
“…This suggests that minor amputations do not negatively impact the daily walking activity of patients with DFU (8). Additionally, although we only had a small subsample of DFU patients wearing a non-removable knee-high offloading device, our findings indicate that unlike their significant effect on reducing high plantar pressures, these gold standard devices may not limit daily steps when compared to other offloading devices as much as previously thought (5,9). Overall, these findings indicate that patients with DFU are significantly less active in terms of daily walking activity than patients with DPN and DM.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This suggests that minor amputations do not negatively impact the daily walking activity of patients with DFU (8). Additionally, although we only had a small subsample of DFU patients wearing a non-removable knee-high offloading device, our findings indicate that unlike their significant effect on reducing high plantar pressures, these gold standard devices may not limit daily steps when compared to other offloading devices as much as previously thought (5,9). Overall, these findings indicate that patients with DFU are significantly less active in terms of daily walking activity than patients with DPN and DM.…”
Section: Discussionmentioning
confidence: 63%
“…Studies have now confirmed that high plantar pressure is a risk factor for developing DFU in people with DPN ; however, in contrast, other studies have identified that it is actually low daily activity that is a risk factor for developing DFU in people with DPN . Subsequently, these low daily activity findings have many hypothesising that interventions that gradually increase daily activity in people with DPN – in combination with appropriate offloading of high plantar pressures – may also improve their rehabilitation, physical fitness, plantar tissue health and prevention of DFU .…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that patients included in our study were older compared with the German Health Update 2009 survey which could be 1 explanation for this discrepancy. Differences between subjects with or without DFS could be explained by mobility restrictions (eg, inability to stand or walk, or therapeutic offloading) resulting from acute DFS or the fear of foot ulcer recurrence . In our analysis, the number of patients stated to be smokers did not differ between subjects with or without DFS (Figure A,B).…”
Section: Discussionmentioning
confidence: 63%
“…Physical activity is a broad term, whereas the term exercise refers to structured or planned activities. Any type of exercise and physical activity has been validated to prevent or at least delay the development of T2D and reduce the risk of comorbidities associated with diabetes . Many exercise studies report that while exercise treatment programmes alone may not necessarily result in significant body weight loss, programmes of sufficient intensity and physical activity reduce the risk of progression to T2D in high‐risk populations .…”
Section: Physical Activitymentioning
confidence: 99%